The p.Thr11Met mutation in c19orf12 is frequent among adult Turkish patients with MPAN. (June 2017) - Olgiati, Simone; Doğu, Okan; Tufekcioglu, Zeynep; Diler, Yunus; Saka, Esen; Gultekin, Murat; Kaleagasi, Hakan; Kuipers, Demy; Graafland, Josja; Breedveld, Guido J.; Quadri, Marialuisa; Sürmeli, Reyhan; et al.
Abstract: Introduction: Mutations in the C19orf12 gene cause mitochondrial membrane protein associated neurodegeneration (MPAN), an autosomal recessive form of neurodegeneration with brain iron accumulation (NBIA). A limited number of patients with C19orf12 mutations, particularly those with adult onset of symptoms, have been reported. Methods: We sequenced the entire coding region of C19orf12 in 15 Turkish adult probands with idiopathic NBIA. We also performed haplotype analysis in families with a recurrent C19orf12 mutation. Clinical features were collected using a standardized form. Results: Nine of our 15 probands (60%) carried the homozygous c.32C > T mutation in C19orf12 (predicted protein effect: p.Thr11Met). This homozygous mutation co-segregated with the disease in all affected relatives available for testing (16 homozygous subjects). Haplotypes across the C19orf12 locus were identical for a very small region, closest to the mutation, suggesting an old founder, or, two independent founders. The clinical phenotype was characterized by adult onset in most cases (mean 24.5 years, range 10–36), and broad spectrum, including prominent parkinsonism, pyramidal signs, psychiatric disturbances, cognitive decline, and motor axonal neuropathy, in various combinations. On T2- or susceptibility weighted-MRI images, all patients displayed bilateral hypointensities in globus pallidus and substantia nigra, without an eye-of-the-tiger sign; however, hyperintense streaking of the medial medullary lamina between the external and internal parts of globus pallidus was observed frequently. Conclusion: The C19orf12 p.Thr11Met mutation is frequent among adult Turkish patients with MPAN. These findings contribute to the characterization of this important NBIA form, and have direct implications for genetic testing of patients of Turkish origin. Graphical abstract: Highlights: MPAN is an autosomal recessive form of NBIA, caused by C19orf12 mutations. We report a series of nine Turkish families with adult onset MPAN. A single homozygous C19orf12 mutation (p.Thr11Met) was the disease cause. Parkinsonism, in combination with other neurological signs, was frequently observed. This single mutation is a prominent cause of MPAN in adult patients of Turkish origin.